Komponen Kimia Asap Cair Hasil Pirolisis Limbah Padat Kelapa Sawit - Haji, Abdul Gani (Jurnal Rekayasa Kimia & Lingkungan, 2013)
Chemical components of liquid smoke which is produced via pyrolisis of palm oil solid waste have been analyzed by using gas chromatography mass spectroscopy (GC-MS). Solid waste consists of shell, empty fruit bunch, and palm fiber. Solid waste was obtained from palm oil manufactory in Tanjung Semantok, Aceh province. The objective of this research was to investigate the chemical components in liquid smoke obtained from various palm oil solid waste. Sample was pyrolyzed at 500C for 5 hours by using tube furnace reactor type 21100 which is equipped by thermolyne as temperature adjustment. The yield of pyrolysis from shell, empty fruit bunch and palm fiber are 52,02; 29,59; and 34,88%, respectively. The results showed that 27; 13 and 11 compounds of chemical were observed in liquid smoke obtained by pyrolysis of shell, empty fruit bunch, and palm fiber, respectively. Overall, acetic acid and phenol are the highest concentration of chemical obtained in this research.